Biogenic synthesis of nano-biomaterial for toxic naphthalene photocatalytic degradation optimization and kinetics studies. (April 2017) - Muthukumar, Harshiny; Gire, Ashish; Kumari, Meena; Manickam, Matheswaran
Abstract: Zinc Oxide (ZnO) and Iron (Fe x)-Zn1–x O (x = 0, 0.5, 1 and 2 wt%) doped ZnO nanoparticles were synthesized using Amaranthus dubius aqueous leaf extract as a reducing agent. The physicochemical properties of the nanoparticles such size, shape, surface area and band energy were determined by analytical techniques. The characterization confirmed that FeZnO were spherical shape with wurtzite phase structure, smaller size, and large surface with less aggregation. The photocatalytic efficiency of ZnO and FeZnO were evaluated by degradation of naphthalene. The effects of various operating parameters including solution pH, photocatalyst and naphthalene concentration on the degradation efficiency and the rate of degradation were investigated. The degradation efficiency and rate of degradation of FeZnO was higher than ZnO photocatalyst. The results confirmed the degradation rate of naphthalene follows the pseudo-first order kinetics. From experimental results, FeZnO can be effectively used in environmental safe applications for pollutant treatment. Graphical abstract: Highlights: Biosynthesis of FeZnO Nps was simple, rapid, economic and effective method. Synthesis of NPs using A. dubius resulted with good yield and no toxic by-products. A. dubius mediated ZnO and Fe doping ZnO NPs have good physicochemical properties. Photocatalytic activity of biomediated NPs were tested by naphthalene degradation. Highest degradation of 93% for 40 ppm naphthalene was achieved under UV- light.